2017
DOI: 10.1111/fwb.12908
|View full text |Cite
|
Sign up to set email alerts
|

Omnivory and stability in freshwater habitats: Does theory match reality?

Abstract: Abstract1. Omnivory, feeding at more than one trophic level, is a prevalent feature of freshwater ecosystems. Understanding where and when omnivory is important, its relevance for sustaining diversity, and the effect it may have on ecosystem responses to disturbances, are necessary for effective management of freshwater ecosystems.2. The many theoretical predictions of the effects of omnivory are often contradictory, and empirical studies aimed at understanding omnivory have been difficult and contingent on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
96
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 128 publications
(269 reference statements)
10
96
2
1
Order By: Relevance
“…In an IGP system, two predators share a food source (shared prey), thereby acting as competitors. The feeding of an IG predator may have important influence on community persistence (Stouffer & Bascompte, 2010) and stability (Neutel et al, 2007;Wootton, 2017). The feeding of an IG predator may have important influence on community persistence (Stouffer & Bascompte, 2010) and stability (Neutel et al, 2007;Wootton, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an IGP system, two predators share a food source (shared prey), thereby acting as competitors. The feeding of an IG predator may have important influence on community persistence (Stouffer & Bascompte, 2010) and stability (Neutel et al, 2007;Wootton, 2017). The feeding of an IG predator may have important influence on community persistence (Stouffer & Bascompte, 2010) and stability (Neutel et al, 2007;Wootton, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides changes in community composition (e.g. the omnivore feeds predominantly on one trophic level) will favour coexistence and increase the stability of food webs (Wootton, 2017). In general, factors that decrease the strength of omnivorous trophic interactions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Omnivory is ubiquitous in freshwaters, and in highly disturbed environments because consumers can shift their diet when resource availability varies (Fagan, 1997, in Wootton, 2017. Empirical studies have shown that intermediate levels of trophic omnivory increase food-web stability (Denno and Fagan, 2003;Thompson et al, 2012), and may therefore be selected for in highly disturbed environments.…”
Section: Trophic Omnivory From Predators Drives Changes In Fclmentioning
confidence: 99%
“…We suggest that because predators feed on different resources depending on the disturbance regime, maintaining the spatial heterogeneity in disturbance within a floodplain can result in overall weaker trophic interactions between predators and consumers. Additionally, by shifting their diets, omnivorous predators may enable depleted consumer populations to better recover from environmental disturbance, resulting in the same stabilising effect in time (Abrams and Fung, 2010;Singer & Bernays, 2003;Wootton, 2017). Additionally, by shifting their diets, omnivorous predators may enable depleted consumer populations to better recover from environmental disturbance, resulting in the same stabilising effect in time (Abrams and Fung, 2010;Singer & Bernays, 2003;Wootton, 2017).…”
Section: Trophic Omnivory From Predators Drives Changes In Fclmentioning
confidence: 99%
“…Food web stability, here defined as temporal constancy, is a fundamental characteristic of ecosystems (Worm & Duffy, ) that can be profoundly affected by the presence of omnivores—organisms that feed on more than one trophic level (Pimm, ; Pimm & Lawton, ). Omnivory is common in food webs across a broad range of habitats, including freshwater systems (Thompson, Dunne, & Woodward, ; Thompson, Hemberg, Starzomski, & Shurin, ; Wootton, ). Omnivores reduce the strength of consumer–resource links by shunting some of the energy up the omnivore–resource pathway and away from the consumer–resource pathway (McCann, Hastings, & Huxel, ).…”
Section: Introductionmentioning
confidence: 99%